Nutrition Communication for The End stage Renal Disease Patients - Kwanpracha, Songsuda; Sridee, Supaporn; Towkeaw, Wittayathorn (Arts of Management Journal, 2023)
This research was a qualitative research using in-depth interviews with the objectives of this research were to study The Nutrition Communication for The End-stage Renal Disease Patients in terms of 1) nutrition communication management for The End-stage renal disease patients, 2) nutrition communication strategies for The End-stage renal disease patients, and 3) approaches for the development of nutrition communication for The End-stage renal disease patients. The key informants were chosen through purposive sampling comprising The End-stage renal disease patients and relatives who underwent dialysis at the Hemodialysis Center, Prachaksinlapakhom army hospital, Udon Thani Province and Hemodialysis Center Krissivara army hospital, Sakon Nakhon Province, personnel directly responsible for nutrition communicating to the End-stage renal disease patients in the hemodialysis center and qualified experts in health communication. Data were analyzed by descriptive drawing conclusions. The results showed that 1) Nutrition communication management for The End-stage renal disease patients consists of the nutrition communication management process for The End-stage renal disease patients starts and the nutrition communication management model. 2) Strategies for driving nutrition communication to be successful within the specified time frame and goals include: (1) Motivational strategies; (2) Persuasive strategies; (3) Engagement strategies; and (4) Knowledge attitudes and behaviors strategies. 3) Guidelines for the development of nutrition communication management for The End-stage renal disease patients as for nutrition communication management, it must be systematized. There must be sufficient study of related problems, information, and patient knowledge covering all patient groups to provide a communication management process and communication management model, including communication strategies that will be used to achieve goals. 4) The proposal for relevant departments must emphasize the linkage of inter-agency communication management.